Clinical and Morphological Features of Dysplasia and Early Gastric Cancer in the Patients with Autoimmune Gastritis - A. S. Tertychnyy; N. V. Pachuashvili; D. P. Nagornaya; T. L. Lapina; E. A. Losik; A. B. Ponomarev; P. V. Pavlov; A. P. Kiryukhin; A. A. Fedorenko; D. D. Protsenko; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to analyze a series of cases of dysplasia and early gastric cancer developed in patients with autoimmune gastritis (AIG), and to identify their clinical and morphological features.Materials and methods. The study included six cases of detection of early gastric cancer on the background of AIG. Four out of six patients underwent endoscopic treatment, and in three out of six cases patients underwent endoscopic mucosectomy with dissection in the submucosal layer. One patient underwent endoscopic surgery in 2017, he continues annual dynamic follow-up without signs of tumour recurrence. A female patient with type 1 neuroendocrine tumour and mild dysplasia is awaiting treatment.Results. In five out of six patients with AIG, the localization of lesions prevailed in the stomach body, while all detected tumours were early ones, and according to the immunophenotype — of a gastric type. The presented cases of tumours were not accompanied by hyperplasia of neuroendocrine cells directly in the area of the tumour itself, but only in the surrounding gastric mucosa. Additionally, several cases of early gastrointestinal stromal tumours were found, which were characterized by low proliferative activity and had small sizes.Conclusion. The predominance of pseudopyloric metaplasia in the surrounding mucosa allows us to consider pseudopyloric metaplasia as a potentially significant change in the gastric mucosa of patients with AIG that may precede the development of gastric cancer.